Functions of Lebak Swamp Before and After Landfills in Jakabaring South Sumatra - M Edi Armanto; R.H. Susanto; Elisa Wildayana (Sriwijaya Journal of Environment, 2017)
The research aimed to analyze the functions of lebak swamp before and after landfills and to seek some alternative management approaches in Jakabaring South Sumatra. The research used quantitative and qualitative approaches. The research area description was assisted with interpretation of landsat images. The research was using survey method and interviews with local people. Two major functions of lebak swamp are ecological functions and non-ecological functions. Before landfills (1988), ecological function of lebak swamp was very dominant (91.64%) and non-ecological functions was about 8.36% meaning that the human intervention was only 8.36%, so lebak swamp has very high resilience capability to recover its ecosystem. After landfills (2016), that ecological functions are reduced becoming 53.88% and non-ecological functions increased to 46.12%.  The region is still save enough for office and housing because the ecological functions (greening areas) occupy an area of more > 30%. In 2030, ecological functions will decrease about 15.53%, while the non-ecological functions will increase around 84.47%. Although in 2016 Jakabaring is still environmentally safe, if we analyze more deeply and intensively, Jakabaring will be vulnerable to man-made disasters such as potential of floods and droughts, sedimentation, migration and dependency on other local staple food.Keywords: Functions, lebak swamp, landfills, Jakabaring, South Sumatray